2013
DOI: 10.1177/030089161309900124
|View full text |Cite
|
Sign up to set email alerts
|

Leptomeningeal Metastasis from Prostate Cancer

Abstract: Aims and background Metastatic prostate carcinoma commonly involves bones and extrapelvic lymph nodes, with occasional visceral deposits. Central nervous system involvement is unusual and particularly the occurrence of leptomeningeal metastasis (LM) is extremely rare, with few cases described in the medical literature. The clinical presentation is characterized by multifocal neurological deficit and the prognosis is generally dismal, with survival ranging between 3 and 6 months. We report on a patient affected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 23 publications
2
20
0
1
Order By: Relevance
“…Leptomeningeal metastases of prostate cancer are extremely rare; they are found in autopsy in approximately 5% of patients with systemic prostate cancer. In a study of genitourinary cancers with leptomeningeal metastases, Yu et al reported an antemortem prevalence of less than 0.03% [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Leptomeningeal metastases of prostate cancer are extremely rare; they are found in autopsy in approximately 5% of patients with systemic prostate cancer. In a study of genitourinary cancers with leptomeningeal metastases, Yu et al reported an antemortem prevalence of less than 0.03% [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…81,82 Nonspecific markers can be strong, indirect indicators of neoplastic meningitis, but none are sensitive enough to improve on the cytological diagnosis. 5 Epithelial-associated glycoprotein is present in up to 90% of neoplastic meningitis cases.…”
mentioning
confidence: 99%
“…This fact seems very relevant according to two aspects. Firstly, in reviewed literature are described possible mechanisms of invasion that are present in solid tumors at higher levels in leptomeningeal location when beginning is sacrum, or blood spread or direct involvement of intra-dural extra-cord component [5,10] which would explain our case. And secondly, this figure is not described in the reviewed literature in any prostate cancer, so we consider that is a singular fact different from the published ones before and, in our opinion, could be one step closer to progression of disease.…”
Section: Discussionmentioning
confidence: 91%